Preparation and characterization of pineapple leaf fiber/poly lactic acid-based biocomposite - Challabi, Ahmed Jaafar Hussein (2019)
In this work, biocomposite from Polylactic acid (PLA) and Pineapple leaf fiber (PALF) was prepared with different fiber loadings 10-50 wt%. The composite was prepared via melt mixing process followed by hot press. Superheated steam (SHS) treatment at various temperature (190 - 230°C) and treatment time (30 - 120 min) have been applied on the fiber to enhance the surface adhesion between the polymer and the fiber. The best condition was at 220°C for 60 min as reflected by the tensile strength of the composite. Additionally, epoxidized palm oil (EPO) was added in the biocomposite as plasticizer at different percentages (1-5 wt%) to overcome the brittleness of the PLA and improve the performance of the biocomposite. A notable enhancement was observed in tensile strength with the addition of 1 wt% of the EPO. The SHS treated fiber at 220°C for 60 min showed better characteristic compared to the untreated fiber. In term of chemical composition, the treated fiber showed a higher content of cellulose and lignin with lower content of hemicellulose. The FTIR results indicated the partial removal of the hemicellulose from the SHS treated fiber. Thermal stability of the SHS treated fiber was improved based on TGA thermogram. The XRD results showed higher crystallinity for the SHS treated fiber compared to the untreated fiber. Moreover, the SEM micrographs proved the removal of the impurities from the SHS treated fiber. It can conclude from these results that the SHS treatment successfully modified the chemical compositions and microstructure of fiber. In term of fiber loading the highest tensile strength was obtained when 30 wt% of fiber loading was used. The results of the incorporation of the SHS treated fiber into the biocomposite showed the effectiveness of SHS treatment in increasing the PALF surface roughness due to the elimination of surface impurities and hemicellulose. The tensile, flexural and impact properties were notably improved by the presence of SHS PALF. Dimensional stability of the biocomposite showed a reduction in water uptake and thickness swelling of the biocomposite. additionally, the scanning electron microscopy analysis showed enhancement in interfacial adhesion between the PLA and the treated PALF. In the case of incorporation of EPO into the biocomposite. The results showed that 1 wt% of EPO showed a significant improvement in the properties of the biocomposite. Tensile strength and tensile modulus as well as flexural and impact strengths were improved. Moreover, with increasing of the EPO content into the biocomposite it showed increment in the elongation at break. The scanning electron microscopy showed improvement in the interfacial adhesion as well with 1 wt% of EPO into the biocomposite. In conclusion, this study proved the possibility of using agricultural waste crops to work as a filler into the polymer matrix, and SHS can be used to treat the fiber to improve the interfacial adhesion between fiber and matrix.